Proses Penciptaan Manusia dalam Perspektif Al-Qur’an dan Ilmu Pengetahuan (Analisis Intertekstualitas Julia Kristeva) - Al Mujaddi, Lalu Riastata; Janhari, M. Nurwathani (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2024)
Lately, in the midst of shocks about rationality, attempts to rationalize the teaching of scripture have become interesting studies, such as the efforts of Shah Waliyullah who tried to rationalize the miracle of Prophet Musa as in the form of the splitting of the Red Sea to become the ebb and flow of seawater. However, these efforts are not accompanied by seeking a dialectical connection between the views of the scripture and the scientific findings themselves. So departing from this background, this research seeks to find transposition models regarding human creation in the eyes of the Qur’an and science by using Julia Kristeva’s theory of intertextuality. The results of this study are that there are four models of transposition between the arguments of the Qur’an and science regarding human creation, namely, modification, haplology, and parallelism. Thus, scientific findings in the current era, especially the creation of humans, take inspiration from the holy book, especially the Qur’an, which is the material object in this paper.